An N, N′-diethylformamide solvent-induced conversion cascade within a metal–organic framework single crystal. Issue 44 (4th May 2020) - Chen, Jing; Chao, Meng-Yao; Yan Liu,; Xu, Bo-Wei; Zhang, Wen-Hua; Young, David J.
Abstract : A two-dimensional metal–organic framework undergoes four-step single-crystal to single-crystals conversions, including a three-step DEF-induced cascade conversion to shuttle back to its original connectivity. Abstract : Crystals of a two-dimensional (2D) metal–organic framework (MOF) [Cd3 (BTB)2 (DEF)4 ]·2(DEF)0.5 (1 ; BTB = benzene-1, 3, 5-tribenzolate; DEF = N, N ′-diethylformamide) immersed in a solution of trans -1, 2-bis(4-pyridyl)ethylene (BPEE) yields an interpenetrated three-dimensional (3D) MOF of [Cd3 (BTB)2 (BPEE)(H2 O)2 ]·(BPEE)· x Sol (2 ). Crystals of MOF 2, in turn, undergo a cascade conversion when immersed in DEF, yielding [Cd3 (BTB)2 (BPEE)1.8 (DEF)0.9 (H2 O)0.8 ]· x Sol (3a ) over 100 seconds and [Cd3 (BTB)2 (BPEE)2 (DEF)2 ]· x Sol (4 ) after one hour, before finally shuttling back to MOF 1 after six hours.